A CROSS-SECTIONAL STUDY OF PERCEPTIONS, PRACTICES AND CHALLENGES OF EXCLUSIVE BREASTFEEDING AMONG EMPLOYED MOTHERS ATTENDING BUEA REGIONAL HOSPITAL, BUEA, CAMEROON. - Etane, Amaka; Mbafor, Brain; Isiko, Isaac; Amaka, Shekina-Rhoda Chioma; Asingwire, Jackson Micheal; Agunwa, Blessing Onyinyechi (Student's Journal of Health Research Africa, 2024)
Background Even though the WHO emphasizes exclusive breastfeeding for six months, many mothers struggle to apply it. This has been blamed on different perceptions of its importance, which has long gone far from affecting the practice. While many women accept the concept, they may face several challenges in its implementation. This study aimed to assess the perceptions, practices and challenges employed mothers face in exclusive breastfeeding at the Buea Regional Hospital in Cameroon. Methodology This was a cross-sectional descriptive study involving 106 employed mothers with children aged zero to two years at Buea Regional Referral Hospital in Cameroon. The quantitative data were collected via structured questionnaires from November 2023 to June 2024. Data analysis and cleaning were carried out via Microsoft Excel 2016 and SPSS version 20. Results The findings showed that most (79.26%) employed mothers had the right perception of exclusive breastfeeding; nevertheless, only 47% of them carried out the practice. This is due to various challenges they face in exclusive breastfeeding practices. The main challenges faced were difficulties combining work and breastfeeding (88.7%), a busy work schedule (87.7%) and social pressure to introduce water and artificial food (87.7%). Conclusion A significant number of mothers had good perceptions of exclusive breastfeeding, while social pressure, working while breastfeeding and busy work schedules were significant barriers to exclusive breastfeeding. Targeted interventions such as increasing leave time, ensuring a reduction in workload and working hours and developing antennal and postnatal policies about exclusive breastfeeding by the government and other employers to promote exclusive breastfeeding among employed mothers are needed. Recommendation Authorities at various job sites reduce the workload and working hours of breastfeeding women with babies younger than 6 months.